The impact of the psychodynamic model of depressive symptoms, psychological resilience, and egoism on the well-being among college students: a hybrid three-stage Fuzzy Delphi and structural equation modeling methodology - Wang Ting; Peng Qian; Sui Xiaohan (Frontiers in Psychology)
BackgroundThe rising prevalence of depressive symptoms among college students has raised significant concerns regarding their mental and physical wellbeing. Grounded in psychodynamic theory, this study examines how depressive symptoms, psychological resilience, and egoism collectively influence psychological wellbeing. While existing literature acknowledges these factors independently, their integrated effects remain underexplored. This research addresses this gap by proposing psychological resilience as a mediator and egoism as a moderator, offering a novel theoretical framework for understanding student wellbeing dynamics in higher education contexts.MethodsThe study employed a mixed-methods approach, combining expert validation with large-scale student data. Ten specialists evaluated wellbeing determinants via a Fuzzy Delphi questionnaire. Quantitative analysis involved 1,336 students from a Chinese public university, with data collected through validated scales. Structural equation modeling (SEM) tested hypotheses regarding: (1) depressive symptoms' direct effects, (2) resilience's mediating role, and (3) egoism's moderating influence. The robust methodology enabled simultaneous examination of these interrelated factors while controlling for academic and social stressors.ResultsThe findings demonstrate a direct correlation between depressive symptoms and students' well-being, alongside a predominantly positive indirect effect of psychological resilience and egoism on psychological well-being, primarily linked to the advantageous impact of alleviating depressive symptoms among college students. This study's findings demonstrate the detrimental effect of students' depressive symptoms on their well-being in education, implementing psychological resilience and egoism as strategic interruption tools.ImplicationsThis research provided empirical evidence and thorough statistical analysis demonstrating the simultaneous presence of both positive and negative effects, facilitating the resolution of existing discrepancies in literature. This research introduced a novel instrument for evaluating student well-being, facilitating further investigations inside the university educational context from a fresh research perspective.